2005
DOI: 10.1176/appi.ajp.162.12.2233
|View full text |Cite
|
Sign up to set email alerts
|

Regional Deficits in Brain Volume in Schizophrenia: A Meta-Analysis of Voxel-Based Morphometry Studies

Abstract: This review implicates the left superior temporal gyrus and the left medial temporal lobe as key regions of structural difference in patients with schizophrenia, compared to healthy subjects. The diversity of regions reported in voxel-based morphometry studies is in part related to the choice of variables in the automated process, such as smoothing kernel size and linear versus affine transformation, as well as to differences in patient groups. Voxel-based morphometry can be used as an exploratory whole-brain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

95
676
13
23

Year Published

2009
2009
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 1,036 publications
(816 citation statements)
references
References 79 publications
95
676
13
23
Order By: Relevance
“…Neuroimaging studies indicate that schizophrenia is associated with neuroanatomical abnormalities, with robust evidence of reduced GM volume in a number of cerebral regions [9,10]. In particular these studies demonstrated volumetric reductions in the whole brain, in the prefrontal cortex and in the superior and medial temporal lobes [4,[11][12][13][14]. These neuroimaging findings are also supported by post-mortem studies [15,16].…”
Section: Introductionmentioning
confidence: 66%
See 2 more Smart Citations
“…Neuroimaging studies indicate that schizophrenia is associated with neuroanatomical abnormalities, with robust evidence of reduced GM volume in a number of cerebral regions [9,10]. In particular these studies demonstrated volumetric reductions in the whole brain, in the prefrontal cortex and in the superior and medial temporal lobes [4,[11][12][13][14]. These neuroimaging findings are also supported by post-mortem studies [15,16].…”
Section: Introductionmentioning
confidence: 66%
“…Studies of patients with schizophrenia demonstrate robust volumetric reductions in multiple brain regions and particularly in the prefrontal cortex and of the superior and medial temporal lobes and in the anterior cingulate [4,[11][12][13][14].…”
Section: Effects Of Antipsychotic Medication On Structural Neuroimagimentioning
confidence: 99%
See 1 more Smart Citation
“…While hippocampal atrophy is profound in AD, and AD is possibly the most common cause of hippocampal atrophy, AD is not the only disorder associated with hippocampal atrophy. Disorders such as schizophrenia [10], traumatic brain injury [11], frontotemporal dementia [12], epilepsy [13] and even depression [14] have been associated with some degree of hippocampal volume loss. Sensitivity and specificity values for hippocampal vMRI in AD are commonly reported in the literature relative to healthy elderly patients, but in clinical practice, the comparison group is rather different and consists of patients with other causes of memory impairment.…”
Section: Evaluating Use Of Vmri In the Clinical Settingmentioning
confidence: 99%
“…However, there also remains variability across studies in the observed magnitude and distribution of such local volume reductions (Shenton et al, 2001;Shepherd et al, 2012). Some of the most replicated findings suggest grey-matter volume is reduced across large networks, differentially involving frontal, temporal, limbic, thalamic and striatal regions (Fornito et al, 2009;Honea et al, 2005). Regional grey-matter volume is influenced by interacting genetic and environmental factors (Wright et al, 2002;Cannon and Keller, 2006) expressed through cytoarchitectural differences (Hof et al, 2003;Schmitt et al, 2008).…”
Section: Introductionmentioning
confidence: 99%